Decay times of transitionally dense specularly reflecting meteor trails and potential chemical impact on trail lifetimes - Hocking, Wayne K.; Silber, Reynold E.; Plane, John M. C.; Feng, Wuhu; Garbanzo-Salas, Marcial (Annales geophysicae (1988), 2016)
Studies of transitionally dense meteor trails using radars which employ specularly reflecting interferometric techniques are used to show that measurable high-temperature chemistry exists at timescales of a few tenths of a second after the formation of these trails. This is a process which is distinct from the ambient-temperature chemistry that is already known to exist at timescales of tens of seconds and longer in long-lived trails. As a consequence, these transitionally dense trails have smaller lifetimes than might be expected if diffusion were the only mechanism for reducing the mean trail electron density. The process has been studied with four SKiYMET radars at latitudes varying from 10 to 75° N, over a period of more than 10 years, 24 h per day. In this paper we present the best parameters to use to represent this behaviour and demonstrate the characteristics of the temporal and latitudinal variability in these parameters. The seasonal, day–night and latitudinal variations correlate reasonably closely with the corresponding variations of ozone in the upper mesosphere. Possible reasons for these effects are discussed, but further investigations of any causative relation are still the subject of ongoing studies.